This Must be the Place: A Holistic Approach to the Development of Boiotian Religious Sites (700-300 BCE) - van Wijk, Roy (Tekmeria, 2024)
In this article I aim to clarify how specific cult sites emerged in southern Boiotia by employing a holistic approach, combining the phenomenological investigations favoured by the recent Spatial and Sensorial Turn with a functionalist understanding of these locations. Understanding how the natural environment provided the impetus for the deliberations on divine presences at these sites forms the first step; a second layer of analysis considers the strategic locations of these places, the political powers willing to invest in the development of the sanctuaries, such as elites or communities, and the paths alongside which these places lay. I will look at how the chosen cult sites – the Apollo cult at Delion, the Ismenios temple at Thebes, the Galaxion and the Kabeirion in the Teneric Plain – were either transformed into sites of trans-local importance due to the investment or take-over from neighbouring larger communities, and how this aimed to create key religious hubs throughout the region that aimed to fortify communal interactions across southern Boiotia between 700 and 300 BCE.